Personalization - An Efficient Technique to Sustain Growth of an E-Commerce and Promotional Websites, Using Emerging Technologies - Negi, Mukesh (International Journal of Computer Sciences and Engineering, 2025)
E-commerce business has surmounted rapidly in the past few years. Flipkart, Amazon, Snapdeal and Shopclues are excellent citation of same. Flipcart was founded in 2007 by two IITn's only, and today it is among the top 3 e-commerce companies over a span of just seven years. Consistent growth of an organization is depend on the robust strategy predestined by the upper management, especially when you have swingeing competitors in front of you. Most of the giant e-commerce companies has adopted emerging IT technologies to align their business for sustainable growth, but still they are struggling in some of the segments, such as Personalization, where customer expectations, likes and dislikes are changing expeditiously day by day [1][2]. Personalization is a technique, where the front page of a website, which also called persona, is portrayed disparately for each customer in pursuance to the products they are interested only. This is one of the best strategy ever, to attract new customers, retain existing one, and to increase e-transactions on a website